Strategi Service Gratis Kendaraan Bermotor Roda Dua Sebagai Pemberdayaan Masyarakat Desa Roworejo, Purworejo, Jawa Tengah - Aci Primartadi; Suyitno Suyitno; Dwi Jatmoko (Journal of Social Responsibility Projects by Higher Education Forum, 2020)
The problem with service partners is that there are many people who want motor vehicle maintenance services to be carried out properly. The purpose of this training activity is to provide maintenance and repair services for motorcycle owners, the implementation of motorcycle services is done by participants registering motorbikes to the administration, motorbikes serviced in accordance with the request of the vehicle owner, after being serviced re-checking by the service advisor, and the last one is returned to the vehicle owner. The free service is carried out in the village hall Roworejo, district Grabag, Kab Purworejo. The results of the implementation of this activity the community feels helped and this activity can run well, this can be seen in the absence of complaints from the community related to vehicles that have been serviced